(untitled) (Journal of Pharmaceutical Negative Results, 2023)
COVID-19 is the highly communicable disease which is being announced as pandemic by WHO. The disease has already impacted the economies of big nations like China, Italy, United states etc and now this disease is hitting our developing country i.e. India too. COVID-19 or Corona virus is human to human spread disease and thus social distancing is the only measure which everyone can take to minimize its spread. National lockdown is the measure taken by Government to create distance among people. But what will be the probable impact of this lockdown on different sectors of our country. This paper aims to analyze impact of COVID-19 on the educational sector of India.